Photoprotective property and cytotoxicity of polar extracts of three species of Maytenus native to the Southwest of Bahia - Pereira, Rosângela Santos; Pereira, Rafael Santos; Aguiar, Rosane Moura; Lemos, Gisele da Silveira; Vieira Filho, Sidney Augusto; de Oliveira, Djalma Menezes (Scientia Plena, 2020)
Maytenus acanthophylla, M. rigida and M. truncata (Celastraceae) are used in the traditional medicine of Chapada Diamantina and Southwest Bahia, Brazil. The infusion and decocto of its leaves are used in the treatment of inflammation and gastric disorders. In this context, it is important to identify chemical and biological properties that reinforce this traditional use. The objective of this study was to determine the total phenolic and flavonoid content by the Folin-Ciocalteau method, the photoprotective property by in vitro spectrophotometric method and the acute toxicity by the mortality index of Artemia salina, of polar extracts of these three Maytenus species. It was observed that the species have similar levels of total phenolic and flavonoid. The presence of compounds containing chromophore groups, which absorb radiation in the UV region between 290 and 320 nm, gives the extracts promising sun protection factors. In the tests with A. salina, the median lethal concentration values were high (≥1000.0 µg/mL) indicating the low toxicity of these extracts. The results contribute to the knowledge of the polar extracts of the three Maytenus species of the Southwest of Bahia, to the validation of the therapeutic properties of these plants and opens perspectives of new studies of photoprotection.